A collaborative physical layer security scheme - Dimitrios Efstathiou (Institute of Advanced Engineering and Science, 2019)
High level of security is essential in wireless 5G communications. The last few years there has been an increase in research interest in the potential of the radio channel’s physical properties to provide communications security. These research efforts investigate fading, interference, and path diversity to develop security techniques for implementation in 5G New Radio (NR). In this paper, we propose a collaborative scheme to existing physical layer security schemes, taking advantage of the characteristics of the OFDM technique. An OFDM symbol includes the pilot subcarriers, typically essential for the pilot channel estimation process performed at the legitimate receiver. In this work we propose the positions of the subcarriers to change on every OFDM symbol following a probability distribution known only to the legitimate transmitter and legitimate receiver. An eavesdropper, does not have access to the information of the pilot subcarriers positions so, it performs blind channel estimation. The theoretical analysis is based on the information theoretic problem formulation and is confirmed by simulations. The performance metrics used are the secrecy capacity and the outage probability. The proposed scheme is very simple and robust, strengthening security in multimedia applications.